Effect of cryotreated electrodes on the machining efficiency of titanium alloy during EDM: a comparative study. (25th September 2022) - Bhaumik, Munmun; Maity, Kalipada
Electro discharge machining (EDM) is one of the most promising nonconventional machining processes. It can machine any conductive material irrespective of its hardness having no direct contact between workpiece and tool. Cryotreatment is introduced in the machining field to boost tool life as well as to lessen the production cost. In this study, a comparison study has been performed during EDM of titanium grade 6 alloy using untreated and cryotreated brass, copper and zinc electrodes. The EDM efficiency has been measured by means of tool wear rate (TWR), surface roughness (Ra ), radial overcut (ROC) and material removal rate (MRR). A metallographic analysis has been done for the untreated and cryotreated electrode surfaces. Lower TWR and better precision of machined surface can be achieved using cryotreated electrodes rather than untreated electrodes. Cryotreated electrodes provide better surface finish compared to the untreated electrodes. A microstructural analysis also has been performed for the EDMed surfaces.